Hypothyroid heart: myxoedema as a cause of reversible dilated cardiomyopathy. (14th October 2015) - Madan, Nidhi; Tiwari, Nidhish; Stampfer, Morris; Schubart, Ulrich
Abstract : Hypothyroidism may cause several cardiac manifestations including conduction abnormalities, pericardial effusion, decreased myocardial contractility and accelerated coronary atherosclerosis. Although cardiac output is reduced in hypothyroidism, frank heart failure (HF) is relatively rare because of the low peripheral oxygen demand. Several mechanisms have been postulated in hypothyroid-induced HF, including genomic as well as non-genomic actions of thyroid hormone. Dilated cardiomyopathy (DCM) of other aetiologies is usually progressive, and is associated with significant morbidity and mortality. We report a case of DCM associated with severe hypothyroidism with marked improvement on restoration of euthyroid state. Our case is unique in that the patient had no known risk factors for cardiac disease and experienced marked improvement despite being on minimal doses of HF medications, illustrating the relationship between hypothyroidism and development of left ventricular dysfunction, and its reversible nature with restoration of euthyroid status.